Physicochemical properties of canola oil, olive oil and palm olein blends - Roiaini M. (2017)
Oil blending has been recognized as one of the most potent solution in producing vegetable oils with good storage stabilities and optimum fatty acids compositions. This study was conducted to identify the best oil blends in terms of physicochemical properties between canola, olive and palm olein oil. Canola and olive oils were blended at different ratios of 80:20, 60:40, 50:50, 40:60, and 20:80. Palm olein is stable against rancidity and oxidation thus the above blends were mixed with 20% palm olein. The 80:20 canola: olive blend shows the best properties after being mixed with 20% palm olein compared to other blends. It passed the cold stability test and has significantly the lowest cloud point of 6.0oC (p<0.05) which means it can be stored at low temperature (7oC). This blend also has significantly high iodine value of 116.04 gI2/100g (p<0.05), low peroxide content of 17.97 meq O2/kg and has significantly the lowest free fatty acid value of 0.16% (p<0.05). Fatty acid composition has shown that it has high unsaturated oleic acid, C18: 1 (58.83%) and relatively high ratio of linolenic acid (5.24%) - linoleic acid (16.50%) compared to other oil blends. Therefore, the oil blend of 80:20 (canola: olive) with 20% palm olein is recommended for deep-frying and can be kept longer due to its stability.